Pobreza, desigualdade de renda, FNE e transferências constitucionais: uma análise para o Nordeste brasileiro - Chaves, Adelson Belchior (2008)
This dissertation aims at analyzing the existent relationship among Poverty, Income Inequality, Fundo Constitutional de Financiamento do Nordeste – FNE (a kind of regional development source), the three main constitutional transferences (FPE, FPM and FUNDEF), Education (indicated by the Average Years of Study from People who are 25 or older), and the average income per capita through the elasticity obtained from those variables in relation to the poverty verified in the Brazilian´s Northeast post - Plano real (an economical plan). For this purpose, there have been developed two log-log econometric models, based on a panel data methodology, whereas one shows the indigence (extreme poverty) dependent variable and the other shows the poverty variable. The results reveal that only the first model has been shown statistically significant for all variables. As for the analyzed historical series (1994 - 2005), it has been found out that the observed signs are the ones expected: a raise of incomes, transferences, average years of study and of FNE contribute to reduce the poverty in the Northeast Region. On the other hand, an income concentration contributes to raise the number of people with revenues under the adopted poverty line.